First record of parasitoids of the pink hibiscus mealybug, Maconellicoccus hirsutus (Hemiptera: Pseudococcidae), in Colombia - MONTES-RODRÍGUEZ, JOSÉ MAURICIO (Revista Colombiana de Entomología, 2012)
Two species of parasitoids, Anagyrus kamali and Gyranusoidea indica (Hymenoptera: Encyrtidae), associa ted with the pink hibiscus mealybug Maconellicoccus hirsutus (Hemiptera: Pseudococcidae), are reported for the first time, in urban areas of the municipalities of Cucuta and Los Patios, in the department of Norte de Santander, Colombia.